Second brain: reviewing the gut microbiome’s role in lifestyle diseases - Hindol Ray; Janatum Khatum; Srijan Haldar; Priyanka Bhowmik (BioTechnologia)
The recent COVID-19 pandemic has highlighted another silent pandemic: lifestyle diseases. Conditions, such as cardiovascular diseases, anxiety, and type 2 diabetes (T2D), are increasingly becoming public health threats, affecting even younger populations worldwide. In recent years, extensive research has uncovered the pivotal role of the human gut microbiome in various aspects of human physiology, including metabolism, cellular homeostasis, immune defense, and disease development. The gut microbiome, often referred to as the “second brain,” is now recognized as a key player in health and disease. Lifestyle factors such as diet, mental health, stress, exercise, and others significantly influence the composition of the gut microbiome. Imbalances in this composition, termed “dysbiosis,” have been linked to a wide range of diseases, including cancer, cardiovascular diseases, obesity, T2D, asthma, and neurological disorders like Alzheimer’s and Parkinson’s disease. These findings underscore the profound influence of gut microbiome health on overall well-being. A working understanding of the gut microbiome’s composition and its impact on disease processes is crucial for the advancement of personalized or precision medicine. This review article aims to explore recent advancements in the field, shedding light on how the gut microbiome contributes to the development and prognosis of lifestyle diseases.